2018
DOI: 10.2320/matertrans.m2018156
|View full text |Cite
|
Sign up to set email alerts
|

Evolution Behavior of Hydrogen-Induced Nano Voids in Al–Zn–Mg–Cu Aluminum Alloys under Loading

Abstract: Synchrotron X-ray nanotomography, which offers a state-of-the-art resolution, has been applied for the 3D observations of hydrogen induced nano voids under different strain levels in AlZnMgCu aluminum alloys. A great number of nano voids are initiated uniformly across the whole specimen during a loading process. The average diameter and number density of initiated nano voids is 300 nm and 5 © 10 15 m ¹3 , respectively. No evidence has been observed that the formation of nano voids results in the propagation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Furthermore, the growth or merging of nanovoids caused by hydrogen is not seen even before fracture, suggesting that nanovoids do not play a dominant role in inducing quasicleavage cracks in Al-Zn-Mg-Cu aluminum alloys 2 . In addition, neither growth nor coalescence of hydrogen-induced nanovoids are observed even just before fracture, indicating that nanovoids do not behave as the dominant factor of hydrogen-induced quasicleavage cracks in Al-Zn-Mg-Cu aluminum alloys 64,65 . For grain boundaries, it has been reported that if large amounts of hydrogen are enriched at the aluminum grain boundary, hydrogen-induced debonding can occur, analogous to the precipitate interface 29 .…”
Section: 𝜃 T 𝑖 1 − 𝜃 Tmentioning
confidence: 93%
“…Furthermore, the growth or merging of nanovoids caused by hydrogen is not seen even before fracture, suggesting that nanovoids do not play a dominant role in inducing quasicleavage cracks in Al-Zn-Mg-Cu aluminum alloys 2 . In addition, neither growth nor coalescence of hydrogen-induced nanovoids are observed even just before fracture, indicating that nanovoids do not behave as the dominant factor of hydrogen-induced quasicleavage cracks in Al-Zn-Mg-Cu aluminum alloys 64,65 . For grain boundaries, it has been reported that if large amounts of hydrogen are enriched at the aluminum grain boundary, hydrogen-induced debonding can occur, analogous to the precipitate interface 29 .…”
Section: 𝜃 T 𝑖 1 − 𝜃 Tmentioning
confidence: 93%
“…where Eb is the trap binding energy ( the trap binding energy of each trap site is summarized in Table . 3 [24][25][26]43,44]), R is the gas constant (8.31 J mole -1 K -1 ), T is the absolute temperature, 𝜃 is the occupancy of the interstitial sites and 𝜃 is the occupancy of other trap sites. The total hydrogen concentration, 𝐶 , which represents the sum of the hydrogen stored in the normal interstitial lattice and all the trap sites is expressed as:…”
Section: Hydrogen Repartitioning Among Various Trap Sites During Defo...mentioning
confidence: 99%
“…In addition, the growth behavior of nanovoids of Al-9.9Zn-2.3Mg-1.4Cu alloy has been analyzed using imaging-type tomography [57] . The nanovoids are uniformly distributed in the strain-localized region, and the accumulation and coalescence of nanovoids was not observed during deformation.…”
Section: D Crack Morphologymentioning
confidence: 99%